Hypoxia conditioning for high-altitude pre-acclimatization - Burtscher, M.; Millet, G. P.; Burtscher, J. (Journal of Science in Sport and Exercise, 2022)
Purpose Main purposes of pre-acclimatization by hypoxia conditioning (HC) are the prevention of high-altitude illnesses and maintenance of aerobic exercise performance. However, robust evidence for those effects or evidence-based guidelines for exposure strategies, including recommendations to ensure safety, are largely lacking. Therefore, we summarize the current knowledge on the physiology of acclimatization to hypoxia and HC with the aim to derive implications for pre-acclimatization strategies before going on high-altitude treks and expeditions.